Refining The Dengue Vulnerability Assessment Based on Dengue Vulnerability Framework Malaysia (DVFM): Descriptive and Panel Data Analysis - Zuliana Azwa Zulkifli; Azeem Fazwan Ahmad Farouk; Dayang Haszelinna Abang Ali; Norhayati Mokhtar (Department of Public Administration, Universitas Negeri Surabaya, 2022)
This study refining the dengue vulnerability assessment using DVFM to describes the vulnerability of dengue in Malaysia during the period of 15 years to identify high-low risk areas among sample of studies (except Wilayah Persekutuan Putrajaya). The dengue reported cases in Malaysia were analyzed using the data provided by the Disease Control Division Vector, Ministry of Health Malaysia (MOH) from 2003-2017. As per literature, factors influencing the vulnerability to infectious disease outbreak were identified as population density, urbanization, medical care workforce, medical care infrastructure, public health delivery, safe water and sanitation as well as economic strength. This framework was tested using empirical cases of dengue outbreak in Malaysia. The dataset used was obtained from widely available data (from the Department of Statistics Malaysia (DOSM) and Health Indicator Report by MOH). From 2003-2017, 829, 299 cases have been reported in Malaysia. The highest number was recorded in 2015 (63198, Selangor). The key findings from this assessment included the states with their vulnerability and actual dengue reported cases. The results also concluded that the framework prediction did not match the actual outbreak reported. Recently in Malaysia, the reported cases have increased steadily in most areas. The surveillance and control strategies should be strengthened especially for areas with the most vulnerable to dengue outbreak without deprioritizing the least vulnerable state. Further research should be conducted to explore other drivers that may reflect the vulnerability of dengue outbreak.